ELECTRIC MODELS OF SEMI-CONDUCTOR MEASURING CONVERTERS - V. A. Sychik; N. N. Ulasiouk; V. S. Shumilo (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика, 2005)
The paper examines electric models of semi-conductor measuring converters. It is noted that main types of electric macro-models used for modeling multipurpose semi-conductor measuring converts should be considered approximate macro-models developed on the basis of a simplified initial circuit at a component level and formal macro-models based on formal approximation of external characteristics of multipurpose measuring converters.